Development of a 127Xe calibration source for nEXO. (1st July 2022) - Lenardo, B.G.; Hardy, C.A.; Tsang, R.H.M.; Nzobadila Ondze, J.C.; Piepke, A.; Triambak, S.; Jamil, A.; Adhikari, G.; Al Kharusi, S.; Angelico, E.; Arnquist, I.J.; Belov, V.; et al.
Abstract: We study a possible calibration technique for the nEXO experiment using a 127 Xe electron capture source. nEXO is a next-generation search for neutrinoless double beta decay (0 νββ ) that will use a 5-tonne, monolithic liquid xenon time projection chamber (TPC). The xenon, used both as source and detection medium, will be enriched to 90% in 136 Xe. To optimize the event reconstruction and energy resolution, calibrations are needed to map the position- and time-dependent detector response. The 36.3 day half-life of 127 Xe and its small Q-value compared to that of 136 Xe 0 νββ would allow a small activity to be maintained continuously in the detector during normal operations without introducing additional backgrounds, thereby enabling in-situ calibration and monitoring of the detector response. In this work we describe a process for producing the source and preliminary experimental tests. We then use simulations to project the precision with which such a source could calibrate spatial corrections to the light and charge response of the nEXO TPC.